PERUBAHAN PERILAKU EKS TENAGA KERJA WANITA DALAM KONTEKS KOMUNIKASI DAN INTERKONEKSI - Irpan Irpan (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2018)
This article discusses the behavior change of ex-female workers who lead to ordinary personalities to be extraordinary. Changes in the behavior of ex-migrant workers not only arise when they are in the country they are occupying, but arise from negative treatment factors obtained from the employer, sexual harassment and various other problems. Despite various cases and problems affecting TKW, there are still many people who still wish to become migrant workers. These problems are increasingly interesting when the people of Keruak Sub-district whose professions are diverse. From the results of observations and preliminary studies, it was shown that the professions of the Keruak District residents worked as odd jobs, farmers, fshermen and a small number as traders, government employees and private employees. The level of education of the citizens is more at the Elementary level. In fact, the enthusiasm of the Keruak District community to become immigrant workers abroad is still large. Many people in Keruak Sub-district choose to become Female Laborers as an alternative to improve the economy.